2009
DOI: 10.1007/s11356-009-0219-0
|View full text |Cite
|
Sign up to set email alerts
|

Landscape-scale distribution and persistence of genetically modified oilseed rape (Brassica napus) in Manitoba, Canada

Abstract: Given the large-scale factors driving the spread of escaped transgenes, localised co-existence measures may be impracticable where they are not commensurate with regional dispersal mechanisms. To be effective, strategies aimed at reducing contamination from GM crops should be multi-scale in approach and be developed and implemented at both farm and landscape levels of organisation. Multiple stakeholders should thus be consulted, including both GM and non-GM farmers, as well as seed developers, processors, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
80
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 36 publications
(54 reference statements)
4
80
0
1
Order By: Relevance
“…A 10-year survey (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002), along road verges of a motorway revealed that most quadrats showed transient populations lasting one to four years (Crawley and Brown, 2004). These data and data from other demographic studies indicate a substantial turnover of populations of feral oilseed rape: only a small percentage of populations occurs at the same location over successive years, whereas the majority appears to die out rapidly (Crawley and Brown, 1995, 2004;Charters et al, 1999;Peltzer et al, 2008;Elling et al, 2009;Knispel and McLachlan, 2009;Nishizawa et al, 2009;Squire et al, 2011). However, if habitats are disturbed on a regular basis by anthropogenic activities such as mowing, herbicide applications or soil disturbance, or natural occurrences such as flooding, then feral populations can persist for longer periods (Claessen et al, 2005a;.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…A 10-year survey (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002), along road verges of a motorway revealed that most quadrats showed transient populations lasting one to four years (Crawley and Brown, 2004). These data and data from other demographic studies indicate a substantial turnover of populations of feral oilseed rape: only a small percentage of populations occurs at the same location over successive years, whereas the majority appears to die out rapidly (Crawley and Brown, 1995, 2004;Charters et al, 1999;Peltzer et al, 2008;Elling et al, 2009;Knispel and McLachlan, 2009;Nishizawa et al, 2009;Squire et al, 2011). However, if habitats are disturbed on a regular basis by anthropogenic activities such as mowing, herbicide applications or soil disturbance, or natural occurrences such as flooding, then feral populations can persist for longer periods (Claessen et al, 2005a;.…”
mentioning
confidence: 63%
“…Because feral oilseed rape is more prevalent in areas with a high frequency of oilseed rape cultivation (Squire et al, 2011), along high-traffic roadsides (Crawley andBrown, 1995, 2004;Knispel and McLachlan, 2009), and in the proximity to seed handling, storage and processing facilities (Yoshimura et al, 2006;Peltzer et al, 2008), repeated seed immigration from both agricultural fields and transport (as fresh seed spills) has been considered the main source contributing to population persistence, countering high extinction rates at a local scale.…”
Section: Replenishment With Fresh Seed Spillsmentioning
confidence: 99%
See 3 more Smart Citations